Effect of domestic effluent, agricultural and industrial pollution on aquatic macroinvertebrates with emphasis on chironomidae (diptera) at community, individual and molecular levels. - Al-Shami, Salman Abdo Ali (2011)
Kelimpahan dan kepelbagaian makroinvertebrata serta parameter air dikaji di lima sungai Lembangan Sungai Juru di utara semenanjung Malaysia; Sungai Ceruk Tok Kun (CTKR), Sungai Pasir (PR), Sungai Permatang Rawa (PRR), Sungai Kilang Ubi (KUR) dan Sungai Juru (JR).